Prototype Peringatan Banjir Berbasis Internet of Things - Khalisah Khalisah; Imam Muslem; Heri Gustami (Jurnal Ilmu Komputer Aceh, 2026)
Flooding is a disaster that frequently strikes Indonesia and causes various negative impacts on the community. Generally, there are two categories of flooding events: flooding in areas not normally submerged in water and flooding caused by overflowing rivers due to water volume exceeding the capacity of the existing river flow. Parameters often used as data to monitor and analyze changes are river water levels during certain seasons as an early warning effort for natural disasters such as flooding. Currently, monitoring river levels is still carried out manually using a water level scale installed on the riverbank, similar to a measuring instrument. Therefore, direct monitoring of the numbers indicated by the scale is necessary. Information obtained by the community is also still relatively inadequate. Therefore, by designing and building a river water level monitoring system based on IoT (Internet of Things), it is hoped that it can provide a solution to this problem. This system utilizes an HC-SR04 Ultrasonic sensor to measure the distance between the sensor and the object using ultrasonic waves. Data obtained from the sensor will be sent to an ESP32 DEV KT V1 microcontroller connected to the internet, so that users can access it through the Telegram application on their mobile phones.